Ensaios sobre o Índice de Desenvolvimento Educacional dos alunos da Universidade da Integração Internacional da Lusofonia Afro-Brasileira (UNILAB) - Santos, Antônio Célio Ferreira dos (2020)
The main purpose of this dissertation is to analyze the so-called academic achievement index of students who entered the Universidade da Integração Internacional da Lusofonia Afro- Brasileira (UNILAB) in 2018. The dissertation is divided into two parts, namely two essays. A major merit of the first essay, Academic standard differentials from UNILAB students measured by means of the Quantum Regression, lies in identifying what kind of particular (due to quantil index effect) factor contributes to the proper ranked grades performed by the students. As a remarkable result, the on-campus modality showed to be a positive parameter as for the academic achievement index (highest index applying to students with best academic achievements), having the better performance women students as compared with men students. In contrast, a result related to the explanatory variable “lives in Redenção” showed to be unexpected, this fact basically rests on the individual characteristics to foreign students The second essay, Academic success disparities from UNILAB quota and non-quota students, aims at verifying by means of the Propensity Score Matching (PSM), entropy balancing included, whether exists (or not) conflictual academic achievement disparities relatively to quota and non-quota students. It is in it highlighted that quota students were better ranked, given their index was approximately 77,152 as compared with non-quota students, whose academic index counted 76.075.